Recent progress in the research about Propionibacterium acnes strain diversity and acne: pathogen or bystander?. (5th October 2016) - Kwon, Hyuck Hoon; Suh, Dae Hun
Abstract: Recent progress has steadily reported the existence of the diverse strains of Propionibacterium acnes, and these studies have contributed to the elucidation of their contradictory roles between normal commensals and pathogens. In this review, the authors aimed to provide an update on the recent understanding of research about P. acnes strain diversity and acne, analyzing the potential implications for clinical applications. Before the era of genomic research, P. acnes was known to be distinguished based on serological agglutination tests, cell wall sugar analysis, or fermentation traits. Since the complete genome sequence of P. acnes was first deciphered, genetic studies based on sequence data have expanded with the introduction of more refined and precise DNA‐based typing methods, including multilocus sequence typing and metagenomics. These sophisticated techniques have revealed that P. acnes consists of phylogenetically distinct cluster groups with various pathogenic traits, including elicitation of inflammation, protein secretome profile, and unique distribution patterns in various skin loci. In following large‐scale studies from patients' acne samples have revealed that specific sequence types are included within the phylogenetic divisions and further suggested that particular P. acnes strains play an etiologic role in acne while others are associated with health, providing a firm platform for evidential‐based research into the exact role of this organism in acne. We strongly believe that future research would provide fruitful results in not only clarifying the apparent controversy with respect to roles of P. acnes but also developing therapeutic drugs by pinpointing specific targets of the pathogenic strain only.